Pharmacist’s clinical evolution: implementation in a university hospital with the use of electronic health record - Trindade, Marianne Teixeira; Minateli, Milene Machado (HU Revista, 2024)
Introduction: The act of documenting in the medical records the activities related to pharmacotherapeutic monitoring has been emphasized by societies and organizations of hospital pharmacists over the years in several countries, thereby reinforcing the need to orderly record their activities through writing standards to optimize care and enhance recognition among the multidisciplinary team. Objective: To develop semi-structured models to implement pharmaceutical progress in electronic medical records in the pediatric unit of the University Hospital at the Federal University of Juiz de Fora – Minas Gerais. Material and Methods: A descriptive cross-sectional study was conducted with patients admitted to the non-COVID-19 pediatric ward from December 1, 2021, to January 31, 2022, whose clinical activities by the pharmacist were recorded in the electronic medical records. Information from users was collected through medical history and input from other professionals, in addition to evaluating prescriptions and documenting pharmacist-suggested interventions related to identified inconsistencies in dosage, dilutions/diluents, drug interactions, occurrence of adverse reactions, therapeutic duplicity, Y-site incompatibilities, and health education. Results: Fourteen semi-structured models based on the SOAP method (Subjective; Objective; Assessment; Plan) were included and implemented for the application of pharmaceutical progress with standardized recording. During the study period, there were 66 hospital admissions. Of these, 45 were eligible and had records in the electronic document of pharmaceutical history and daily prescription assessment results, whether or not pharmaceutical interventions were present. Conclusion: The study aimed at creating a model for clinical progress notes, aiming to enhance effectiveness and continuity of care in the pediatric sector, as well as to enrich communication and recognize the value of the clinical pharmacist’s service.